Association of Latent Tuberculosis and Vitamin D Levels in Young Individuals: An Exploratory Study - Priyanka; Parul Bhatt; Ayushi Kaur Bedi; Mandira Varma Basil; Monika Sharma; Sadhna Sharma (International Journal of Mycobacteriology)
Background: India has one of the highest prevalence of tuberculosis (TB) incidence, and Vitamin D deficiency is potentially a risk factor. Latent TB infection is the main reservoir of the global burden of TB. Detecting Mycobacterium tuberculosis infection and identifying the risk factors are the first steps toward improving TB control, preventive therapy, and treatment completion. Methods: The present study explores the relationship between latent TB prevalence by QuantiFERON-TB Gold PLUS using interferon-gamma release assay (IGRA) and Vitamin D levels by enzyme immunoassay in 46 young healthy adults. Results: Among the 46 young adults tested, 14 (30.43%) were IGRA positive, 32 (69.56%) were IGRA negative, and 1 (2.17%) had indeterminate results. Among all, Vitamin D deficiency was found to be in 23.91% of individuals (n = 11). The optimal value of Vitamin D was found in 33 individuals (71.73%) and an overdose of Vitamin D was found in 2 individuals (4.34%). We found 23.19% of individuals as IGRA negative but had Vitamin D deficiency (mean = 12 ng/ml) and 4% of individuals as IGRA positive and Vitamin D deficient. The 45.66% of individuals with an optimal range of Vitamin D (mean = 40.77 ng/ml) were IGRA negative. We also observed that 42.85% of IGRA-positive individuals were taking Vitamin D supplements. Conclusion: Although we did not find any significant correlation between Vitamin D deficiency and IGRA-positive individuals, Vitamin D supplements may be helpful in maintaining a healthy state in latent TB individuals.